Simulating the near-field dynamic plume behavior of disposed fine sediments - Gundlach, Jannek; Herbst, Maximilian; Alex, Antje Svenja; Zorndt, Anna; Jordan, Christian; Visscher, Jan; Schlurmann, Torsten (Frontiers in Marine Science, 2024)
Projections of the effects of fine sediment disposals, relevant for managed estuaries and tidally influenced coastal areas, are typically based on numerical far-field models. For an accurate consideration of the disposal itself, near-field models are often needed. The open source near-field model, PROVER-M, simulates the relevant processes of the physics based, dynamic behavior of disposed fine sediments in coastal waters and is applied in this study. First, new small scale laboratory experiments of instantaneous disposals are presented, documenting the dynamic behavior of fine material disposed in shallow waters. Second, results of the PROVER-M model are shown for disposals in three different settings: (1) a field-scaled study complementary to the laboratory set-up, (2) a parametric study of sequentially varied model input and (3) a far-field model coupling for estimation of the PROVER-M impact. By comparing results of the laboratory experiments to the PROVER-M model, the physical behavior of PROVER-M is successfully validated. The impact of the ambient setting and dredged material parameters is evaluated by the PROVER-M simulations, where the results show non-linear, complex interdependencies of the input parameters on disposal properties in dependence of ambient site conditions and material composition. In this context, limits of the model application are assessed and critically discussed. Finally, an exemplary coupling to a far-field model based on a real set of disposals in the tidally influenced Weser estuary (Germany) illustrates the potential impact of PROVER-M for assessing far-field suspended sediment concentration (SSC), with 30 increased maximum SSC values of up to 10%.